DC$1 (BDC Converters for Future Renewable Energy Systemss - Priyadarshi, Neeraj; Bhoi, Akash Kumar; Bansal, Ramesh C.; Kalam, Akhtar; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
The book presents the analysis and control of numerous DC-DC converters widely used in several applications such as standalone, grid integration, and motor drives-based renewable energy systems. The book provides extensive simulation and practical analysis of recent and advanced DC-DC power converter topologies. This self-contained book contributes to DC-DC converters design, control techniques, and industrial as well as domestic applications of renewable energy systems. This volume will be useful for undergraduate/postgraduate students, energy planners, designers, system analysis, and system governors.
Design and Control of DC-DC Converters in a PV based LVDC Microgrid -- High Gain Buck-Boost Converter for Solar Photovoltaic (PV) System -- Developed Boost Converter With Generalized Quadratic Boosting Cell To Minimize Capacitor Voltage Stresses And Reduce The Cost Of Utilized Capacitors -- Comparative Analysis of Nonlinear SMC Controller with Linear PID Controller for Flyback Converter -- Effect of Irradiance on THD of Neutral Point Clamped Inverter Fed from Pv Cell -- Bidirectional Interleaved Switched Capacitor Dc-Dc Converter for Renewable Energy Applications -- LUO Converters for Renewable Energy Applications.
Keywords: Electronic circuits; Electronics; Electric power production; Electronic Circuits and Systems; Electronics and Microelectronics, Instrumentation; Electrical Power Engineering; DC-to-DC converters; Renewable energy sources